Comparison of students’ critical thinking ability between PBL and PjBL learning groups on environmental pollution material Phase-E at SMAN 1 2x11 Kayu Tanam - Astuti, Aulia Fuji; Desnita, Desnita; Putra, Amali; Emiliannur, Emiliannur (Universitas Muhammadiyah Mataram, 2024)
21st century learning prepares high school graduates to master critical thinking ability. However, there are still many high school graduates who do not have critical thinking ability. One way to overcome students' low critical thinking ability is to use innovative learning models that prioritize student activity. This research aims to compare the critical thinking abilities of students taught using the Problem-based learning (PBL) and Project-based learning (Pj.BL) models. This study uses a posttest-only control group design and is quasi-experimental in nature. Determination of the sample through the use of a purposive sampling technique. The data obtained is in the form of data resulting from critical thinking ability. The instrument used is a critical thinking ability test instrument in the form of a description test. The data analysis techniques used are normality, homogeneity and hypothesis testing at a significance level (α) = 0.05. Based on data analysis, the results obtained are tcount = 4.552 > ttable = 1.998 which states that H1 is accepted. Based on these results, it can be concluded that the Problem-based learning model is more effective than the Project-based learning model in honing students' critical thinking ability.